Promotion of school-based comprehensive sexuality education: building support from teachers and parents in Thailand. Issue 7 (3rd October 2022) - Chiba, Mina
ABSTRACT: In accordance with the global efforts to promote school-based comprehensive sexuality education (CSE) in developing countries, this study focuses on selected schools in Thailand and explores effective measures to expand parents' and teachers' support for school-based CSE. The research was conducted using semi-structured interviews with school principals and teachers, and group interviews with parents and students. The results of this study revealed that, in areas where there is objection to CSE due to cultural sensitivity, the key to widening support was teachers' and parents' subjective recognition of the positive outcomes of CSE on the students' health and development.